Menschen im Espresso - Vesely, Herbert (Germany, 1958)
In 1962, the proclamation of the Oberhausen Manfesto marked the beginning of the New German Film. This film is one of the films from 1958-1964 produced, directed, photographed or edited by one or more of the filmmakers who signed the manifesto.
The film is contained with other pieces: Schicksal einer Oper 1958, (10 min.), Glühendes Eiland Kreta 1959, (12 min.), Das magische Band 1959, (21 min.), Moskau ruft 1959, (12 min.), Stunde X 1959, (4 min.) (Fragment), Trab Trab 1959, (11 min.), Salinas 1960, (11 min.), Schatten 1960, (10 min.), ".... Geist und ein wenig Glück" 1965, (31min.), Brutalität in Stein 1961, (11 min.), Kommunikation 1961, (11 min.), Notizen aus dem Altmühltal 1961, (17 min.), Plakate der Weimarer Republik 1962, (10 min.), Süden im Schatten 1962, (9 min.), Das Unkraut 1962, (11 min.), Es muß ein Stück vom Hitler sein 1963, (11 min.), Anmeldung 1964, (10 min.), Marionetten 1964, (11 min.), Granstein 1965, 13 min., Die Erben von Papas Kino 1968, (27 min.).
Options for the subtitles: French, English, Spanish, Russian, German.